The Use of Nasi Pelleng Local Wisdom as Social Science Teaching Material - Guntur Arie Wibowo; Madhan Anis; Chairuddin; Van Kim Hoang Ha; Aulia Rahman (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
Local knowledge and traditions have a lot of potential as a result of Indonesia's diverse cultural landscape. Several regional Indonesian proverbs have been used in the classroom as teaching aids. Nasi pelleng, a form of indigenous knowledge, is still hardly ever acknowledged or utilized in the classroom. Making Nasi Peleng traditional knowledge into a tool for teaching social science is thus novel. The purpose of this study is to evaluate the viability of including Nasi Pelleng traditional knowledge in the social science curriculum. Data collection methods for the qualitative approach adopted in this study include observations, recordings, interviews, and other sources that are connected to Nasi Peleng traditional knowledge. Additionally, content analysis is utilized to examine the data gathered. Based on its practical qualities and local wisdom values, the research's findings—which take the form of a presentation of Nasi Peleng's local knowledge—are appropriate for use as social sciences teaching materials. The religious, austere, and cooperative principles found in the Nasi Pelleng heritage can be used as a guide for how to behave in society, and this integration can be one of the attempts.maintaining communal knowledge that is beginning to be lost. Consequences of According to this study, children can learn to live simply and form communities by cooperating and showing respect for one another through the use of educational materials based on the Nasi Peleng tradition. Keywords:  Nasi Pelleng, Local Wisdom, Social Science Teaching Material